FGF2 regulates melanocytes viability through the STAT3-transactivated PAX3 transcription - Dong, L (Nature Publishing Group, 2012)
PAX3 (paired box 3) is known to have an important role in melanocyte development through modulation of microphthalmia-associated transcription factor transcription. Here we found that PAX3 transcriptional activity could be regulated through FGF2 (basic fibroblast growth factor)-STAT3 (signal transducer and activator of transcription 3) signaling in the pigment cells. To study its function in vivo, we have generated a transgenic mouse model expressing PAX3 driven by tyrosinase promoter in a tissue-specific fashion. These animals exhibit hyperpigmentation in the epidermis, evident in the skin color of their ears and tails. We showed that the darker skin color results from both increased melanocyte numbers and melanin synthesis. Together, our study delineated a novel pathway in the melanocyte lineage, linking FGF2-STAT3 signaling to increased PAX3 transcription. Moreover, our results suggest that this pathway might contribute to the regulation of melanocyte numbers and melanin levels, and thereby provide an alternative strategy to induce pigmentation.